Hello, [Your Name]: Why Name‐Based Personalization Enhances Chatbot Effectiveness - Ji Min Lee; Vivian Pontes; Saira Raza Khan; Pham Van Hau (Psychology & Marketing, 2026)
ABSTRACT Organizations increasingly adopt chatbots as strategic tools to engage with consumers and strengthen brand outcomes. This study explores how chatbots that use name‐based personalization in their communications can more efficiently influence consumer behavior towards the brand. Across five experimental studies, we demonstrate that name‐based personalization within chatbot messages enhance perceptions of chatbot sincerity and brand sincerity, leading to more favorable consumer attitudes and higher purchase intentions toward the brand. The effect of personalization on perceived chatbot sincerity is mediated via perceived anthropomorphism. Further, we identify a few boundary conditions for the positive effects of name‐based personalization, namely chatbot performance and perceived overuse of name‐based personalization. These findings contribute to the literature on personalization, anthropomorphism, branding, and the Computers Are Social Actors (CASA) theory, and offer practical implications for marketers seeking to design effective chatbots for brands.